Strategies Of Islamic Education In The Perspektif Of The Quran - Aulyah Rabilla; Nurhayati Nurhayati (Proceeding International Seminar of Islamic Studies, 2019)
Research entitled learning strategies of Islamic educatin in the perspectie of the Quran The problem that arises is that Islamic education is lagging behind other educational institutions, both qualitatively and quantitatively. So that Islamic education is impressed as second class education. It is not surprising that at this time many generations of Muslims are actually studying in non-Muslim educational institutions. One of the cause of this happening is because of inaccucare strategies used in learning in student, especially Islamic learning strategies in the perspective of the Quran. The strategy is very important in teaching and learning activities for students, learning strategies are designed to achieve educational goals. Learning strategies include several things, models, and specific learning techniques. The method used is library research, qualitative. Any methods used in Islamic education learning is very good all, depending on how the teacher teaches it to students, and according to students needs.